Dimension reduction for −Δ1. (6th February 2014) - Amendola, Maria Emilia; Gargiulo, Giuliano; Zappale, Elvira
<x content-type="archive" xml:space="preserve">Abstract</x> A 3D-2D dimension reduction for −Δ1 is obtained. A power law approximation from −Δp as p → 1 in terms of Γ-convergence, duality and asymptotics for least gradient functions has also been provided.